Membangun Karakter Murid Melalui Pendidikan Agama - Pebriana Sirait; Benedikta Tamba; Istoto Raharjo (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Religious Education is an education process that has a purpose to form religious character of the religious tradition to individuals. This formation process includes an understanding of the Holy Book, religious traditions, and moral and spiritual development in accordance with religion culture and tradition. This religious education is the basis for students meditative thinking because it plays an important role in shaping human spiritual and moral development. As writers, we are using the literature review approach in writing this article in order to compile a deep understanding to improve the character education of the people based on the principles of religion culture and tradition. The results of this study confirm that Religious Education can form the students personality and character responsible individuals.